Intellectual Capital and its Influence over the Financial Decisions of Companies - Екатерина Ивановна Тюрина; Илья Олегович Иванинский (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2010)
Current article is an overview of models of influence of intellectual capital over the corporate financial decisions, as a main factor, influencing the value of firms. The importance of intellectual capital has dramatically increased with the transition to the knowledge economy. Inclusion of factors of intellectual capital into the models of corporate financial decisions is a way to increase the quality of analysis.Despite the fact that the influence of the intellectual capital on firms and corporate financial decisions in developed markets of the USA and the Western Europe is a proven fact, the evidence from the emerging markets is still scarce. Current researches of corporate financial decisions rarely include intellectual capital as a factor. Current article demonstrates the results of inclusion of these factors.Results of analysis of early works show negative relationship between intellectual capital and both the level of financial leverage and dividend payout ratio. However, more recent research, considering the efficiency of utilization of intellectual capital, shows that relationship between the efficiency of utilization of intellectual capital and  the level of financial leverage is positive. At the moment there is no direct empirical evidence of relationship between the efficiency of utilization of intellectual capital and  the  dividend policy.